Impact of Trainings on Adoption of Chickpea (Cicer arietinum L.) Production Technology (Indian Journal of Extension Education, 2012)
The study was conducted in Sihora block of Jabalpur district of Madhya Pradesh to identify the impact of Krishi Vigyan Kendra (KVK) training programmes on extent of adoption of chickpea (Cicer arietinum L.) production technology. six villages were selected randomly among chickpea cultivated villages. Out of which, 60 trained farmers and 60 untrained farmers were selected randomly from the similar village so total 120 respondents were taken for investigation. The study revealed that trained farmers had higher extent of adoption of chickpea production technology and untrained farmers had medium extent of adoption of chickpea production technology